Polymer-Metal Bilayer with Alkoxy Groups for Antibacterial Improvement - Idriss, Hazem; Kutová, Anna; Rimpelová, Silvie; Elashnikov, Roman; Kolská, Zdeňka; Lyutakov, Oleksiy; Švorčík, Václav; Slepičková Kasálková, Nikola; Slepička, Petr (Polymers, 2024)
Many bio-applicable materials, medical devices, and prosthetics combine both polymer and metal components to benefit from their complementary properties. This goal is normally achieved by their mechanical bonding or casting only. Here, we report an alternative easy method for the chemical grafting of a polymer on the surfaces of a metal or metal alloys using alkoxy amine salt as a coupling agent. The surface morphology of the created composites was studied by various microscopy methods, and their surface area and porosity were determined by adsorption/desorption nitrogen isotherms. The surface chemical composition was also examined by various spectroscopy techniques and electrokinetic analysis. The distribution of elements on the surface was determined, and the successful bonding of the metal/alloys on one side with the polymer on the other by alkoxy amine was confirmed. The composites show significantly increased hydrophilicity, reliable chemical stability of the bonding, even interaction with solvent for thirty cycles, and up to 95% less bacterial adhesion for the modified samples in comparison with pristine samples, i.e., characteristics that are promising for their application in the biomedical field, such as for implants, prosthetics, etc. All this uses universal, two-step procedures with minimal use of energy and the possibility of production on a mass scale.
Keywords: PEG coating; alkoxy amine; bacterial adhesion; polymer layer; grafting; medical devices; diazotization; titanium; stainless steel